Theater and virtuality : Towards a transgression of the live theatre - González Cid, Liuba (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Digital culture poses a new relationship between theater and society driven by the impact of new technologies, with the consequent displacement of its representational codes: text and staging. From hybrid, virtual and face-to-face models emerge experimental stage creation profiles. However, these relationships between virtuality, technology, innovation and theater have been present throughout its history, virtuality being the consubstantial agent to the scenic fact both in the dramaturgical and in the spectacular.